Characteristics and pathogenicity of Vibrio alginolyticus SWS causing high mortality in mud crab (Scylla serrata) aquaculture in Hong Kong - Kwok, Carsten Tsun-Ka; Yu, Ray Chun-Wai; Hau, Pak-Ting; Cheung, Karry Yuen-Ching; Ng, Iain Chi-Fung; Fung, Joshua; Wong, Ivan Tak-Fai; Yau, Miranda Chong-Yee; Liu, Wai-Man; Kong, Hang-Kin; Siu, Gilman Kit-Hang; Chow, Franklin Wang-Ngai; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionVibrio alginolyticus is a Gram-negative, rod-shaped bacterium belonging to the family of Vibrionaceae, a common pathogen in aquaculture animals, However, studies on its impact on Scylla serrata (mud crabs) are limited. In this study, we isolated V. alginolyticus SWS from dead mud crab during a disease outbreak in a Hong Kong aquaculture farm, which caused up to 70% mortality during summer.MethodsExperimental infection and histopathology were used to investigate the pathogenicity of V. alginolyticus SWS in S. serrata and validate Koch’s postulates. Comprehensive whole-genome analysis and phylogenetic analysis antimicrobial susceptibility testing, and biochemical characterization were also performed. ResultsOur findings showed that V. alginolyticus SWS caused high mortality (75%) in S. serrata with infected individuals exhibiting inactivity, loss of appetite, decolored and darkened hepatopancreas, gills, and opaque muscle in the claw. Histopathological analysis revealed tissue damage and degeneration in the hepatopancreas, gills, and claw muscle suggesting direct and indirect impacts of V. alginolyticus SWS infection.ConclusionsThis study provides a comprehensive characterization of V. alginolyticus SWS as an emerging pathogen in S. serrata aquaculture. Our findings underscore the importance of ongoing surveillance, early detection, and the development of targeted disease management strategies to mitigate the economic impact of vibriosis outbreaks in mud crab aquaculture.